Stablecoins, money market funds and monetary policy - I\~naki Aldasoro; Giulio Cornelli; Massimo Minesso Ferrari; Leonardo Gambacorta; Maurizio Michael Habib (European Central Bank (ECB), 2024)
Using a new series of crypto shocks, we document that money market funds' (MMF) assets under management, and traditional financial market variables more broadly, do not react to crypto shocks, whereas stablecoin market capitalization does. U.S. monetary policy shocks, in contrast, drive developments in both crypto and traditional markets. Crucially, the reaction of MMF assets and stablecoin market capitalization to monetary policy shocks is different: while prime-MMF assets rise after a monetary policy tightening, stablecoin market capitalization declines. In assessing the state of the stablecoin market, the risk-taking environment as dictated by monetary policy is much more consequential than flight-to-quality dynamics observed within stablecoins and MMFs.
Keywords: E50; F30; 330; stablecoins; crypto; Bitcoin; monetary policy shocks; money market funds